Finds of Spanish (Gothic-Mudéjar) Pottery from the Saint Mary of the Castellum and Upper Corner Tower Sites in Dubrovnik (Archaeologia Adriatica, 2012)
This paper analyses finds of Spanish (Gothic-Mudéjar) pottery found at the following sites: the Benedictine Monastery of Saint Mary of the Castellum, and the Upper Corner Tower, both of which are in the historical centre of Dubrovnik. These are rather rare pottery finds that were transported via trade routes from workshops in Valencia and its surroundings. The finds have been dated to the end of the 14th century and also to the 15th century, and are classified as majolica which, in addition to a nontransparent glaze on which decoration was applied, was also glazed with an expensive lustre overing. The pottery testifies to the prosperity and fine taste of certain citizens of Dubrovnik, which was one of the largest maritime, trade and cultural centres on the eastern Adriatic coast in this period.
Keywords: Dubrovnik; Saint Mary of the Castellum; Upper Corner Tower; lustre pottery (lustreware); Spanish (Gothic-Mudéjar) pottery; Spain; Valencia